Therapeutic Argentine Tango Dancing for People with Mild Parkinson’s Disease: A Feasibility Study - Blandy, Laura M.; Beevers, Winifred A.; Fitzmaurice, Kerry; Morris, Meg E. (Frontiers in Neurology, 2015)
Background: Individuals living with Parkinson’s disease (PD) can experience a range of movement disorders. Therapeutic dance is enjoyable and thought to improve mobility, balance and well being in some people with PD. The primary objective of this study was to evaluate the feasibility and safety of a 4 week Argentine tango dance program for people with PD. Methods: Six community dwelling individuals with mild-moderate PD were recruited from Parkinson’s support groups, movement disorder clinics and the Parkinson’s disease Association in Australia. To minimise falls risk, participants were required to be less than 75 years of age and physically independent (Hoehn and Yahr stages I-III). They were also required to speak English. Participants attended a 1 hour dance class at a dance studio twice per week for 4 weeks. A professional dance instructor led and choreographed the classes. Physiotherapists were present to assist participants during the class and served as dance partners as necessary. The primary outcome was feasibility which was determined by measures of recruitment, adherence, attrition, safety (falls, near misses and adverse events) and resource requirements. Secondary measures included the Beck Depression Inventory and the Euroqol-5D, administered at baseline and post intervention. Therapy outcomes pre and post-intervention were analysed descriptively as medians and inter-quartile ranges and using Wilcoxon matched pair signed-rank tests.Results: The Argentine tango dance intervention was shown to be safe, with no adverse events. Adherence to the dance program was 89%. Depression scores improved after intervention (p=0.04). Some challenges were associated with the need to quickly recruitment participants and supplying physiotherapists to act as dance partners. Conclusion: The program was shown to be feasible and safe for people with mild to moderately severe PD.